Shanghai literary imaginings : a city in transformation - Scheen, Lena (Asian cities (Amsterdam, Netherlands), 2015)
This book draws on a wide range of methods--including approaches from literary studies, cultural studies, and urban sociology--to analyze the transformation of Shanghai through rapid growth and widespread urban renewal. Lena Scheen explores the literary imaginings of the city, its past, present, and future, in order to understand the effects of that urban transformation on both the psychological state of Shanghai's citizens and their perception of the spaces they inhabit.